The Impact of Precipitation Regimes on Forest Fires in Yunnan Province, Southwest China. (27th August 2014) - Chen, Feng; Niu, Shukui; Tong, Xiaojuan; Zhao, Jinlong; Sun, Yu; He, Tengfei
Abstract : The amount, frequency, and duration of precipitation have important impact on the occurrence and severity of forest fires. To fully understand the effects of precipitation regimes on forest fires, a drought index was developed with number of consecutive dry days (daily precipitation less than 2 mm) and total precipitation, and the relationships of drought and precipitation with fire activities were investigated over two periods (i.e., 1982–1988 and 1989–2008) in five ecoregions of Yunnan Province. The results showed that precipitation regime had a significant relationship with fire activities during the two periods. However, the influence of the drought on fire activities varied by ecoregions, with more impacts in drier ecoregions IV-V and less impacts in the more humid ecoregions I–III. The drought was more closely related to fire activities than precipitation during the two study periods, especially in the drier ecoregions, indicating that the frequency and the duration of precipitation had significant influences on forest fires in the drier areas. Drought appears to offer a better explanation than total precipitation on temporal changes in fire regimes across the five ecoregions in Yunnan. Our findings have significant implications for forecasting the local fire dangers under the future climate change.